A Study of The Reasons for Deferral of Voluntary Blood Donors at A Tertiary Care Hospital - Attri, Nisha; Margam, Sangita; Mahajan, Anjali (Annals of Pathology and Laboratory Medicine, 2019)
Background: Voluntary blood donation forms the basis of procurement of safe blood from a healthy donor. Donor selection is necessary in addition to the screenings of blood bags for infectious diseases. Deferrals lead to loss of precious blood/components available for transfusion. For preventing this, we should be having knowledge of causes of deferral and their frequency. Methods: The study was conducted in the blood bank of Lokmanya Tilak Municipal Medical College and General Hospital, Sion, Mumbai, India, from January 2017 to July 2018 to determine the incidence of deferrals. The aim of our study is to know the incidence of donors who were deferred from donating blood and to determine the causes of permanent and temporary deferral. Result: A total of 21,433 donors were screened. Out of which, 1134 donors were deferred. The total donor deferral rate was 5.29%; the percentages of deferral being 1.62% for females and 3.67% for males. The deferral was maximum between 18- 40 years of age. The temporary deferral was more common than permanent deferral; the reasons in males being anemia, low blood pressure and underweight. The reasons documented in females being anemia, menstrual history within one week, followed by underweight. The most common reason in both males and females, for permanent deferral was hypertension. Conclusion: Donor deferral rate of 5.29% was found in this study. Females coming forward for blood donation were significantly low. The major causes of deferral were anemia and hypertension.